Supported manganese-based composite material and method for adsorbing and removing organic sulfur in fuel oil by using same

By designing a load-type manganese-based composite material, combining MnOx nanomaterials and carbon molecular sieve CMS, the problems of easy polymerization of traditional adsorbents and low utilization of active components are solved, and efficient removal of organic sulfur from fuel is achieved, reducing operating costs and enhancing the stability of adsorbents.

CN119771341APending Publication Date: 2025-04-08LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510136637.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional MnOx adsorbents have problems such as easy polymerization and low utilization of active components, which leads to high operating costs, low processing efficiency and difficult by-product processing, making it difficult to effectively remove organic sulfur from fuel oil.

Method used

A load-loaded manganese-based composite material is designed, including MnOx nanomaterials and carbon molecular sieve CMS. Through a specific preparation process, the MnOx nanomaterials are combined with carbon molecular sieve CMS to form the MnOx/CMS composite material. The material improves its thermal and chemical stability by calcining treatment.

Benefits of technology

It improves the adsorption capacity and desulfurization efficiency of organic sulfur compounds, reduces operating costs, enhances the stability and sustainability of adsorbents, and makes it have broad application prospects in the field of fuel desulfurization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771341A_ABST
    Figure CN119771341A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of supported manganese-based composite materials, in particular to a supported manganese-based composite material which comprises a MnOx nano material and a carbon molecular sieve CMS, the MnOx nano material is Mn2O3, and the loading capacity of the MnOx nano material is 0.6%-9.1%; the loading capacity of the carbon molecular sieve CMS is 10-60%, the particle size of the carbon molecular sieve CMS material is 1mm, and the carbon molecular sieve CMS material is a cylinder; the MnOx and CMS are compounded, so that the desulfurization efficiency is improved, the operation cost is reduced, the stability and sustainability of the adsorbent are enhanced, and the technical scheme has a wide application prospect in the field of fuel desulfurization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of supported manganese-based composite materials, and in particular to a supported manganese-based composite material and a method for removing organic sulfur from fuel by adsorption thereof. Background Art

[0002] As global awareness of environmental protection increases, sulfur content standards in petroleum products are becoming increasingly stringent. Organic sulfur compounds, such as dibenzothiophene (DBT) and its derivatives, are common sulfides in petroleum. They are not only harmful to the environment, but also cause problems such as adsorbent poisoning during petroleum processing. Therefore, the development of efficient desulfurization technology is of great significance to the petroleum industry.

[0003] Traditional desulfurization methods, such as alkaline washing, adsorption and hydrodesulfurization, have problems such as high operating cost, low treatment efficiency and difficulty in by-product treatment. In recent years, supported adsorbents have attracted widespread attention due to their advantages such as high activity, easy separation and reusability. In particular, manganese oxide MnOx has attracted much attention due to its excellent performance in the adsorption desulfurization process. However, traditional MnOx adsorbents have problems such as easy polymerization and low utilization of active components.

[0004] Therefore, in order to address the above-mentioned problems of high operating cost, low processing efficiency, difficulty in by-product treatment, and easy polymerization and low utilization rate of active components of traditional MnOx adsorbents, a supported manganese-based composite material and a method for adsorbing and removing organic sulfur from fuel can be designed. Summary of the invention

[0005] In order to overcome the problems of high operating cost, low processing efficiency, difficulty in by-product treatment, and easy polymerization and low utilization rate of active components of traditional MnOx adsorbents.

[0006] The technical solution of the present invention is: a supported manganese-based composite material comprising MnO x Nanomaterials and carbon molecular sieves CMS;

[0007] MnO x Nanomaterials are Mn2O3, MnO x The nanomaterial loading is 0.6% to 9.1%;

[0008] The carbon molecular sieve CMS loading amount is 10% to 60%, the particle size of the carbon molecular sieve CMS material is 1 mm, and the carbon molecular sieve CMS material is cylindrical.

[0009] The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material comprises the following steps for deeply removing thiophene sulfides from coking benzene using the supported manganese-based composite material as described above:

[0010] Step 1: Mix the manganese nitrate aqueous solution with the carbon molecular sieve CMS, heat and age in an oil bath, and then filter and dry the reaction product to obtain Mn / CMS;

[0011] Step 2: dissolving manganese nitrate tetrahydrate in deionized water and stirring evenly to obtain a solution containing a Mn(NO3)2 precursor;

[0012] Step 3: Add carbon molecular sieve CMS to the solution containing Mn(NO3)2 precursor, heat and age in a water bath, cool to room temperature after aging, filter out the material, wash and dry to obtain Mn / CMS material;

[0013] Step 4: Place the Mn / CMS material in a crucible and calcine in an air atmosphere to obtain a MnOx / CMS material.

[0014] Preferably, the source of manganese ions is manganese chloride tetrahydrate, manganese acetate tetrahydrate, manganese sulfate tetrahydrate and manganese nitrate tetrahydrate.

[0015] Preferably, the mass ratio of the manganese source to the carbon molecular sieve CMS is 1:2.0-2.9, and the solvent ratio of deionized water to the carbon molecular sieve is 1.5-1:1.

[0016] Preferably, the oil bath aging temperature is 40 to 70° C. and the time is 18 to 24 hours.

[0017] Preferably, the calcination temperature is 3300-500° C., the time is 3-5 hours, the calcination atmosphere is air atmosphere, and the heating rate during the calcination process is 5-10° C. / min.

[0018] The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material comprises the following steps for deeply removing sulfur-containing compounds from low-sulfur fuel using the supported manganese-based composite material as described above:

[0019] Step 1: Add zirconium chloride (ZrCl4) and terephthalic acid (BDC) to N,N-dimethylformamide (DMF), stir magnetically and then continue ultrasonication;

[0020] Step 2: The above solution is transferred to a high-pressure reactor and placed in an oven for reaction; after cooling to room temperature, it is centrifuged and washed with DMF and methanol (CH3OH), and the solid obtained by centrifugation is transferred to an oven and dried overnight to obtain the material UiO-66;

[0021] Step 3: Add ferric chloride hexahydrate (FeCl3·6H2O), gelatin, urea (CH4N2O) and a certain amount of UiO-66 to deionized water, and after magnetic stirring, transfer the above solution to a high-pressure reactor and place it in an oven for reaction and then cool to room temperature;

[0022] Step 4: Collect the precipitate by centrifugation, wash it three times with ethanol and vacuum dry it overnight to finally obtain the material FeOOH / UiO-66.

[0023] Preferably, the oven temperature is 80° C. to 120° C., the heating time is 21 h to 24 h, and the magnetic stirring is performed for 60 min followed by ultrasonication for 20 min.

[0024] Preferably, the content of N,N-dimethylformamide (DMF) is 82 ml, the content of zirconium chloride (ZrCl4) and terephthalic acid (BDC) is 0.8 ml each, the content of ferric chloride hexahydrate (FeCl3·6H2O) is 2.7020 g, the content of gelatin is 0.1000 g, the content of urea (CH4N2O) is 0.6060 g, and the content of deionized water is 100 ml.

[0025] Preferably, the centrifugal speed is 8000 rpm / min, the centrifugal time is 5 min, and the vacuum drying temperature is 65°C.

[0026] Beneficial effects of the present invention: The high specific surface area and porous structure of the carbon molecular sieve significantly increase the number of active sites, which not only increases the contact area between the adsorbent and the reactant, but also promotes the diffusion and adsorption of organic sulfur compounds on the surface of the adsorbent, providing a good basis for the desulfurization reaction. Secondly, the thermal stability and chemical stability of CMS ensure the long-term structure and activity of the adsorbent in the desulfurization reaction, and it can remain stable even under high temperature conditions, which helps to capture and remove the difficult-to-degrade organic sulfur compounds; at the same time, the pore structure and chemical properties of the MnOx / CMS composite material improve the adsorption capacity of sulfur-containing compounds, further improving the desulfurization efficiency; The MnOx / CMS loaded adsorbent also exhibits good reusability and can be restored to activity by simple washing and drying, which not only reduces the cost of desulfurization, but also reduces waste generation, showing environmental friendliness; in addition, due to the physical properties of CMS, the adsorbent is easy to separate and recover from the reaction system for reuse; the synergistic effect between MnOx and CMS further enhances the overall desulfurization performance; therefore, the composite of MnOx and CMS not only improves the desulfurization efficiency, but also helps to reduce operating costs and enhance the stability and sustainability of the adsorbent, making it a technical solution with broad application prospects in the field of fuel desulfurization. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The figure shows the removal efficiency of the supported manganese-based composite material MnOx / CMS at different calcination temperatures of the present invention for removing liquid fuel oil at room temperature;

[0028] Figure 2Shown is the TEM-mapping image of the supported manganese-based composite material MnOx / CMS-400 of the present invention;

[0029] Figure 3 The figure shows the specific surface area of ​​the supported manganese-based composite material MnOx / CMS-400 of the present invention;

[0030] Figure 4 What is shown is the X-ray diffraction pattern of the supported manganese-based composite material MnOx / CMS-400 of the present invention;

[0031] Figure 5 What is shown is the X-ray photoelectron spectrum of the supported manganese-based composite material MnOx / CMS-400 of the present invention;

[0032] Figure 6 The figure shows the efficiency of the supported manganese-based composite material MnOx / CMS-400 of the present invention in removing 100 ppm of fuel oil;

[0033] Figure 7 Shown is a cycle efficiency diagram of MnOx / CMS in the supported manganese-based composite material of the present invention for removing organic sulfur from liquid fuel oil by adsorption at room temperature. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Example 1

[0036] The present invention provides an embodiment: a supported manganese-based composite material, comprising MnO x Nanomaterials and Carbon Molecular Sieve CMS; MnO x Nanomaterials are Mn2O3, MnO x The loading amount of the nanomaterial is 0.6%; the loading amount of the carbon molecular sieve CMS is 10%, the particle size of the carbon molecular sieve CMS material is 1 mm, and the carbon molecular sieve CMS material is cylindrical;

[0037] 5.0 g of manganese nitrate tetrahydrate was dissolved in 30 ml of deionized water until a homogeneous mixture was obtained; 20 g of carbon molecular sieve was immersed in the metal salt solution, aged at 70 °C for 12 hours, and then calcined in air at 300 °C for 3 hours; MnO x / CMS; 5.752 g of lanthanum nitrate was dissolved in 40 ml of deionized water to obtain a homogeneous mixture; 20 g of MnO x / CMS was immersed in a metal salt solution, aged at 80 °C for 24 h, and then calcined in air at 300 °C for 3 h; La2O3 / MnO x / CMS.

[0038] Example 2

[0039] The present invention provides an embodiment: a supported manganese-based composite material, comprising MnO x Nanomaterials and Carbon Molecular Sieve CMS; MnO x Nanomaterials are Mn2O3, MnO x The loading amount of the nanomaterial is 0.6%; the loading amount of the carbon molecular sieve CMS is 10%, the particle size of the carbon molecular sieve CMS material is 1 mm, and the carbon molecular sieve CMS material is cylindrical;

[0040] 0.8 mmol zirconium chloride (ZrCl4) and 0.8 mmol terephthalic acid (BDC) were added to 82 mL N, N-dimethylformamide (DMF), and the mixture was stirred magnetically for 60 min and then ultrasonicated for 20 min. The solution was transferred to a high-pressure reactor and placed in an oven for reaction at 120 °C for 24 h. After cooling to room temperature, the mixture was washed three times by centrifugation with DMF and methanol (CH3OH), and the solid obtained by centrifugation was transferred to an oven and dried at 60 °C overnight to obtain the material UiO-66. 100 mL 2.7020 g of ferric chloride hexahydrate (FeCl3·6H2O), 0.1000 g of gelatin, 0.6060 g of urea (CH4N2O) and a certain amount of UiO-66 were added to deionized water. After magnetic stirring for 60 min, the above solution was transferred to a high-pressure reactor and placed in an oven. After reacting at 80 °C for 21 h, it was cooled to room temperature and centrifuged at 8000 rpm / min for 5 min to collect the precipitate. After washing three times with ethanol, it was vacuum dried at 65 °C overnight to finally obtain the material FeOOH / UiO-66.

[0041] The supported manganese-based composite materials of Examples 1 and 2 and the method for removing organic sulfur from fuel by adsorption thereof not only improve the desulfurization efficiency, but also help to reduce operating costs and enhance the stability and sustainability of the adsorbent, making it a technical solution with broad application prospects in the field of fuel desulfurization.

[0042] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the purpose of the present invention.

Claims

1. Supported manganese-based composite materials, including MnO x Nanomaterials and carbon molecular sieves CMS; MnO x Nanomaterials are Mn2O3, MnO x The nanomaterial loading is 0.6% to 9.1%; The carbon molecular sieve CMS loading amount is 10% to 60%, the particle size of the carbon molecular sieve CMS material is 1 mm, and the carbon molecular sieve CMS material is cylindrical.

2. A method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material, characterized in that The supported manganese-based composite material according to claim 1 is used for deep removal of thiophene sulfides in coking benzene as follows: Step 1: Mix the manganese nitrate aqueous solution with the carbon molecular sieve CMS, heat and age in an oil bath, and then filter and dry the reaction product to obtain Mn / CMS; Step 2: dissolving manganese nitrate tetrahydrate in deionized water and stirring evenly to obtain a solution containing a Mn(NO3)2 precursor; Step 3: Add carbon molecular sieve CMS to the solution containing Mn(NO3)2 precursor, heat and age in a water bath, cool to room temperature after aging, filter out the material, wash and dry to obtain Mn / CMS material; Step 4: Place the Mn / CMS material in a crucible and calcine in an air atmosphere to obtain a MnOx / CMS material.

3. A method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material, characterized in that: The source of manganese ions is manganese chloride tetrahydrate, manganese acetate tetrahydrate, manganese sulfate tetrahydrate and manganese nitrate tetrahydrate.

4. The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material according to claim 2, characterized in that: The mass ratio of the manganese source to the carbon molecular sieve CMS is 1:2.0-2.9, and the solvent ratio of deionized water to the carbon molecular sieve is 1.5-1:

1.

5. The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material according to claim 2, characterized in that: The oil bath aging temperature is 40-70°C and the time is 18-24 hours.

6. The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material according to claim 2, characterized in that: The calcination temperature is 3300-500° C., the time is 3-5 hours, the calcination atmosphere is air atmosphere, and the heating rate during the calcination process is 5-10° C. / min.

7. A method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material, characterized in that: The supported manganese-based composite material according to claim 1 is used for deeply removing sulfur-containing compounds in low-sulfur fuel as follows: Step 1: Add zirconium chloride (ZrCl4) and terephthalic acid (BDC) to N,N-dimethylformamide (DMF), stir magnetically and then continue ultrasonication; Step 2: The above solution is transferred to a high-pressure reactor and placed in an oven for reaction; after cooling to room temperature, it is centrifuged and washed with DMF and methanol (CH3OH), and the solid obtained by centrifugation is transferred to an oven and dried overnight to obtain the material UiO-66; Step 3: Add ferric chloride hexahydrate (FeCl3·6H2O), gelatin, urea (CH4N2O) and a certain amount of UiO-66 to deionized water, and after magnetic stirring, transfer the above solution to a high-pressure reactor and place it in an oven for reaction and then cool to room temperature; Step 4: Collect the precipitate by centrifugation, wash it three times with ethanol and vacuum dry it overnight to finally obtain the material FeOOH / UiO-66.

8. The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material according to claim 7, characterized in that: The oven temperature is 80°C to 120°C, the heating time is 21h to 24h, and the magnetic stirring is performed for 60min followed by ultrasonication for 20min.

9. The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material according to claim 7, characterized in that: The content of N,N-dimethylformamide (DMF) is 82 ml, the content of zirconium chloride (ZrCl4) and terephthalic acid (BDC) is 0.8 ml each, the content of ferric chloride hexahydrate (FeCl3·6H2O) is 2.7020 g, the content of gelatin is 0.1000 g, the content of urea (CH4N2O) is 0.6060 g, and the content of deionized water is 100 ml.

10. The method for removing organic sulfur from fuel by adsorption using a supported manganese-based composite material according to claim 7, characterized in that: The centrifugal speed was 8000 rpm / min, the centrifugal time was 5 min, and the vacuum drying temperature was 65°C.